2019
DOI: 10.3390/nu11092019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Carbohydrate Ingestion on Cognitive Flexibility and Cerebral Oxygenation during High-Intensity Intermittent Exercise: A Comparison between Maple Products and Usual Carbohydrate Solutions

Abstract: Background: The aim of this study was to compare the effects of carbohydrate (CHO) drinks (6% per volume) sweetened with maple (syrup or sap) to a commercial sports drink, glucose, and a control solution (water) on cognitive flexibility during high-intensity intermittent exercise. Methods: Eighty-five active men completed six 3-min bouts at 95% of their maximal aerobic power on a stationary bike, with 3 min of passive rest between efforts. Subjects were randomly allocated to an ingestion condition. Following e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
0
12
1
Order By: Relevance
“…A bitter or sweet taste was previously shown to interact with corticomotor excitability [13] and brain oxygenation [16]. Although, recent results from our laboratory show no difference in brain oxygenation during repeated highintensity cycling bouts with carbohydrate ingestion (including maple products) or water [12]. In the current study, the lower overall appreciation reported with MW ingestion could be associated with the increased perception of sweet taste during the exercise period.…”
Section: Discussioncontrasting
confidence: 49%
“…A bitter or sweet taste was previously shown to interact with corticomotor excitability [13] and brain oxygenation [16]. Although, recent results from our laboratory show no difference in brain oxygenation during repeated highintensity cycling bouts with carbohydrate ingestion (including maple products) or water [12]. In the current study, the lower overall appreciation reported with MW ingestion could be associated with the increased perception of sweet taste during the exercise period.…”
Section: Discussioncontrasting
confidence: 49%
“…Given these results, it appears that fatiguing characteristics of the HIIE, mainly due to a high physiological load (83.5 ± 6.4 % HRmax in our study), transitional bursts of very high intensity exercise period, and the contribution of both aerobic and anaerobic metabolic pathways to energy provision could induce a negative effect on cognitive performance in the earlier bout of exercise. This notion has been supported by findings from Dupuy and Tremblay [14] who claimed a decrease of RT and accuracy during a cognitive flexibility task towards the end of 6 x 3 minutes of heavy cycling exercise. Some neuroendocrinological model issued explanations for this cognitive performance impairment.…”
Section: Discussionmentioning
confidence: 63%
“…First, Welsh et al [12] reported no benefit of CHO feedings on the Stroop color task performance, which requires inhibition of prepotent responses and selecting relevant sensory information [13], during 60 minutes of shuttle running exercise interspaced with a 20-min halftime passive rest period. On the contrary, a recent study by Dupuy et Tremblay [14] suggests a slight reduction of reaction times throughout exercise with CHO ingestion (6%) on cognitive flexibility during a modified Stroop task, measured prior, between and after 3-min bouts of heavy cycling exercise for 36 minutes total duration. It is important to notice that in these two studies cognitive performance was not assessed simultaneously to HIIE exercise, but prior to exercise and during recovery.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The search methods resulted in 67 articles. After removal of duplicates, 15[40-53] articles were identified in PubMed and 5[54-58] new articles in CINAHL. During the initial screening of titles/abstracts, 11 articles were excluded due to HIIE not being the primary experimental protocol performed (n=6), studies not measuring cerebral arteries (n=4) and an animal study (n=1).…”
Section: Resultsmentioning
confidence: 99%